Ways of Knowing:Polymorphism and Co-Substantive Essences in Yolngu Sea Cosmology - Magowen, Fiona (The Australian Journal of Indigenous Education, 2001)
The nature of the relationship between people, land and ancestors in Australia Aboriginal societies has generated ongoing anthropological debate. Since the inception of anthropological studies of Aboriginal religion, the idea of totemism has been used to elucidate the spiritual and physical relationship between these elements. The paper begins with a re-evaluation of the human-ancestor-land complex, focusing particular on theorists of Australian totemism such as Stanner (1966), concerniing Aboriginal religion, and Munn's (1973) seminal explanation of transformations of objects into subjects and subjects into objects in Walbiri ideology.